A practical guide to sample preservation and pre‐PCR processing of aquatic environmental DNA. (12th November 2019) - Kumar, Girish; Eble, Jeff E.; Gaither, Michelle R.
Abstract: Environmental DNA (eDNA) is rapidly growing in popularity as a tool for community assessments and species detection. While eDNA approaches are now widely applied, there is not yet agreement on best practices for sample collection and processing. Investigators looking to integrate eDNA approaches into their research programme are required to examine a growing collection of disparate studies to make an often uncertain decision about which protocols best fit their needs. To promote the application of eDNA approaches and to encourage the generation of high‐quality data, here we review the most common techniques for the collection, preservation and extraction of metazoan eDNA from water samples. Specifically, we focus on experimental studies that compare various methods and outline the numerous challenges associated with eDNA. While the diverse applications of eDNA do not lend themselves to a one‐size‐fits‐all recommendation, in most cases, capture/concentration of eDNA on cellulose nitrate filters (with pore size determined by water turbidity), followed by storage of filters in Longmire's buffer and extraction with a DNeasy Blood & Tissue Kit (or similar) has been shown to provide sufficient, high‐quality DNA. However, we also emphasize the importance of testing and optimizing protocols for the system of interest.